Transformation of Fresh Tomato Into Powder and its Conservation by the Artisanal Drying Method in the Province of Uige in Angola - Kinkela, Nswadi; Mpanda, Kundakama; Metos, Nwadi Nsayi (European Journal of Applied Sciences, 2022)
Tomato is a plant belonging to the Solanaceae family, scientifically named Lycopersicum esculentum Mill. Essential for the agricultural industry; the tomato is one of the most cultivated and consumed used agricultural products by most of the population of the province of Uige in Angola. It has excellent nutritional value, rich in vitamins, lycopene, and mineral salts, and can be eaten fresh or processed. The tomato is essential not only for its nutrients but also for its health benefits [9]. When making field observations, two aspects caught our attention: When large quantities of tomatoes are produced but not sold, we noticed that the rest of the merchandise gets rotted due to their water content. On the other hand, almost all markets and supermarkets in Uige sell fresh tomato and other tomato products (tomato paste, ketchup, etc.). However, there is a shortage of tomato powder in the market. Thus, this research aims to transform fresh tomato into powder, analyze the quality of the powder, conserve it to minimize post-harvest losses, and at the same time offer a different sensory product to the population of Uige. In order to achieve the objective of our research, we have built a small-scale greenhouse for drying fresh tomatoes. The tomato powder was taken to the chemical laboratory of Kimpa Vita University (Uige/Angola) for chemical analysis of the product stored for 75days. Organoleptic analyses, such as glycogen content (reducing sugars), titratable acidity, pH, and moisture content, were carried out. In addition, the identification of some phytochemical substances such as flavonoids, lycopene, anthocyanins, and reducing sugar. The samples analyzed within the 75 days of storage presented the following results: The colour remained light red from day 1 to day 48, and from December 9th to the end of the experiment, it changed to dark red. Odour and taste changed from very good to good. The texture remained powdery. During the identification of chemical substances, we found flavonoids, lycopene, and glycides in the tomato powder As for the physical-chemical parameters, the following averages were obtained respectively: pH: 4.02, acidity in citric acid:0.4%, moisture content: 36.6%, Glucose content:4.46%.